The Role of Islamic Economics and Social Finance during the Covid-19 Pandemic - Syarifuddin Syarifuddin (Budapest International Research and Critics University, 2022)
This research was conducted with the aim of describing several solutions and the role of Islamic social economic and financial policies that can be offered in dealing with the Covid-19 pandemic in Indonesia. This study uses a descriptive qualitative approach with content analysis techniques (content analysis) and library research. The results of the study indicate that among the solutions that can be offered within the framework of the concept and system of Islamic Economics and Social Finance are: (1) by distributing direct cash assistance from zakat, infaq, and alms; (2) by strengthening waqf in the form of cash waqf, productive waqf, sukuk linked waqf and waqf for infrastructure; (3) through leading business capital assistance for the business sector or Micro, Small and Medium Enterprises (MSMEs); (4) through the qardhul hasan scheme; (5) improvement of Islamic economic and financial literacy; (6) through the development of Islamic financial technology.